Pemanfaatan Sampah Plastik Menjadi Ecobrick: Inovasi Mahasiswa KKN Untuk Lingkungan Berkelanjutan di Nagari Guguak Malalo, Batipuh Selatan, Tanah Datar - Esy Maestro; Az-Zahra Yusup Fatimah; Mutiara Cahya Afifah; Ilhamda Zikri; Hani Sakinah Putri; Rieflan Rukia Adzfan (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
The growing problem of plastic waste has become a significant environmental challenge, particularly in rural areas. This study aims to describe the utilization of plastic waste into ecobricks as an innovative initiative by university students during their Community Service Program (KKN) to support environmental sustainability in Nagari Guguak Malalo, Batipuh Selatan Subdistrict, Tanah Datar Regency. A qualitative descriptive method was employed, with data collected through observations, in-depth interviews, and documentation. The findings reveal that the conversion of plastic waste into ecobricks offers not only a practical solution for managing household waste but also raises community awareness regarding the importance of recycling and reducing plastic usage. This innovation has proven effective in empowering local communities, particularly women and youth groups, to actively engage in sustainable environmental activities. Furthermore, the KKN program fosters collaboration between students, village authorities, and local residents in building a cleaner and healthier environment.